ANALISIS SWOT PERKEMBANGAN BATIK KENDAL - Sri Suryaningsum; Raden Hendri Gusaptono; Sri Luna Murdianingrum; Alifa Nida Maharani; Rakyan Widowati Tanjung (Fakultas Ekonomi Universitas Pekalongan, 2020)
This study focuses on the use of SWOT analysis is the selection of the best strategies for the development of Batik Kendal. SWOT analysis is an analysis of the strengths, weaknesses, opportunities, and threats. This analysis is needed to choose a strategy that is suitable for the development of the company. Batik Kendal had experienced a generation breakdown and is now beginning to be preserved again. That the right strategy is needed can be sustainable and known by the wider community. The results of the SWOT analysis are expected to overcome the threats and disadvantages that exist using the opportunities and advantages. With the existence of threats and shortcomings, they can be used as guidelines in improving the quality of the company. Keywords: Development of Kendal Batik, SWOT Analysis, Business Strategy